The Effect of Price Perception, Shipping Costs and Time Pressure on Purchase Decisions of Shopee Flash Sale at Universitas Muhammadiyah Surakarta - Zakiah, Z; Sari, Dhany Efita; Karima, Mutiara; Ahmad, Noor Lela (Proceedings International Conference on Education Innovation and Social Science, 2022)
The goal of this study is to see if price perception, shipping expenses, and time pressure have a positive and substantial impact on purchasing decisions during the Shopee Flash Sale. This study used a survey research design to conduct a comparative causal study (cross sectional survey). 226 Accounting Education Universitas Muhammadiyah Surakarta students who used Shopee Flash Sale were polled. 7 questions for the price perception variable, 9 questions for the shipping cost variable, 6 questions for the time pressure variable, and 8 questions for the Shopee Flash Sale purchase decision variable were distributed via a google form. Multiple linear regression, partial t test, and f test were employed in the data analysis. The findings reveal that 1) there is a relationship between the two variables; and 2) there is a relationship between the two.